2011
DOI: 10.1074/jbc.m110.206722
|View full text |Cite
|
Sign up to set email alerts
|

Glycoside Hydrolase Family 89 α-N-acetylglucosaminidase from Clostridium perfringens Specifically Acts on GlcNAcα1,4Galβ1R at the Non-reducing Terminus of O-Glycans in Gastric Mucin

Abstract: In mammals, ␣-linked GlcNAc is primarily found in heparan sulfate/heparin and gastric gland mucous cell type mucin. ␣-N-Acetylglucosaminidases (␣GNases) belonging to glycoside hydrolase family 89 are widely distributed from bacteria to higher eukaryotes. Human lysosomal ␣GNase is well known to degrade heparin and heparan sulfate. Here, we reveal the substrate specificity of ␣GNase (AgnC) from Clostridium perfringens strain 13, a bacterial homolog of human ␣GNase, by chemically synthesizing a series of disaccha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Similar truncation studies that focused solely on CBM32s 2 to 6 revealed one or more of these CBMs to be able to bind mucin [11]. Notably, constructs of CpGH89 lacking the three most C-terminal CBMs had reduced activity on mucin suggesting an important role for the CBMs in substrate recognition.…”
Section: Introductionmentioning
confidence: 76%
“…Similar truncation studies that focused solely on CBM32s 2 to 6 revealed one or more of these CBMs to be able to bind mucin [11]. Notably, constructs of CpGH89 lacking the three most C-terminal CBMs had reduced activity on mucin suggesting an important role for the CBMs in substrate recognition.…”
Section: Introductionmentioning
confidence: 76%
“…Therefore, the 1,3‐1,4‐α‐ l ‐fucosidase activity produced would enable C. perfringens ATCC 13124 to remove α1,3/4‐fucosyl residues. In addition to α‐ l ‐fucosidases, C. perfringens is able to produce a series of other exo‐glycosidases, including sialidases , α‐ N ‐acetylglucosaminidase , and β‐ N ‐acetylhexosaminidase , to release the terminal sialic acid, α‐GlcNAc, and α‐GalNAc from mucin O ‐glycans. Endo‐β‐galactosidases of C. perfringens are able to remove special terminal glyco‐epitopes on mucin O ‐glycans, such as Galα1‐3Gal, GlcNAcα1‐4Gal, and A/B blood groups .…”
Section: Discussionmentioning
confidence: 99%
“…Clostridium perfringens is a common opportunistic pathogen in human intestine, which can cause gas gangrene, necrotic enteritis, food poisoning diarrhea, and non‐foodborne gastrointestinal infections . This pathogen is able to produce various glycosidases (http://www.cazy.org/) for glycan foraging and some of them have been clone and characterized, including endo‐α‐ N ‐acetylgalactosaminidase , sialidases , α‐ N ‐acetylglucosaminidase , and endo‐β‐galactosidases . There are a few reports up to now about its α‐ l ‐fucosidases.…”
Section: Introductionmentioning
confidence: 99%
“…( Figure S6Aii) These proteoglycans are found on mammalian cells and in mucus (Monzon, Casalino-Matsuda and Forteza, 2006). Also, mucins with similar structures to heparan sulfate/heparin ( a-linked GlcNAC or N-Acetyl-D-glucosamine) are present intestinally and found in PGM (Fujita et al, 2011).…”
Section: Phage Es17 Binds Human Heparan Sulfated Proteoglycansmentioning
confidence: 99%
“…Indeed, the addition of heparanse III, from the soil bacteria Flavobacterium heparinum, which specifically cleaves unmodified (unsulfated) NAc domains (GlcNAc-GlcUA) and NA/NS domains (GlcNS (N-Sulfo-D-Glucosamine) and GlcNAc) of HS, leads to abrogated phage ES17 binding to cells, meaning ES17 was highly specific for this type of glycan (Murphy et al, 2004;Park et al, 2017). Structurally similar mucins to heparan sulfate (Class III type, a-linked GlcNAc) suggest that this protein may also target these intestinal mucins (Ota et al, 1998;Fujita et al, 2011). This interaction is driven by phage ES17's tail fiber protein, which is not related to the hoc proteins or contain an Ig-like fold as predicted from the BAM model.…”
Section: Phage Es17 Kills Expec In the Mammalian Intestinementioning
confidence: 99%